Peningkatan Hasil Belajar PAI dengan Metode Diskusi pada Siswa Kelas IV SD Negeri 15 Rumah Nan XXX - Sari, Elva (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) through the application of the discussion method in class IV at SDN 15 Rumah Nan XXX. This research uses the Classroom Action Research (CAR) design, consisting of two cycles. The results show that the implementation of the discussion method can enhance students’ learning outcomes, with improved active participation and better understanding of the material in the second cycle. Through group discussions, students not only deepen their understanding of concepts but also develop critical thinking skills and the ability to collaborate. The study concludes that the discussion method is effective in improving PAI learning outcomes and can be an alternative teaching method in elementary schools.